Application of √area-concept to assess fatigue strength of AlSi7Cu0.5Mg casted components. (November 2017) - Garb, C.; Leitner, M.; Grün, F.
Highlights: Experimental fatigue strength testing of Sr- and Na-modified AlSi7Cu0.5Mg T6W castings. Application of √area-concept based on Murakami. Model incorporates several specimen locations exhibiting different micro porosity. Abstract: In this paper casted aluminium alloy AlSi7Cu0.5Mg T6W is examined by fatigue strength testing and fractographic analysis of the fractured surfaces to characterise the failure origin. The specimens extracted from cylinder heads differ in their eutectic modification between strontium (Sr) and sodium (Na). Three specimen locations are Sr-modified and one is Na-modified. The fractographic analysis enables the characterisation of the occurred micropore sizes within the different specimen positions. The determination of the micropore sizes is also supported by computed tomography (CT) scans for better understanding of the micropore shapes. Murakami's √area-concept is applied on the four data sets to investigate the dependency of the fatigue strength on the micropore size. For the purpose of increasing the number of data points at the run-out region, two projection methods are presented to consider data points from the finite-life regime. Considering the scatter band of the S/N-curves, a method based on a power equation is selected. The √area-concept is additionally modified to enabling a more precise adjustment on the respective data set. The fractographic analyses show mixed occurrence of slip bands and micropores. To evaluate the application of such mixed cause of failure in the applied approach, a reduced data set without such mixed failure types is compared with the results over the whole data base. The √area-concept over all data points exhibit valid results proofing that the consideration of the mixed causes of failure including slip bands and micropores is acceptable. Comparing the stress levels of fatigue tests with the results from the applied model, on average a conservative behaviour can be noted, whereas almost all assessed data points are within a scatter band of 10% deviation to the mean value of the experiments.